Optimum multi DG units placement and sizing based on voltage stability index and PSO - Jamian, J.J.; Aman, M.M.; Mustafa, M.W.; Jasmon, G.B.; Mokhlis, Hazlie; Bakar, A.H.A.; Abdullah, M.N. (2012)
Optimum DG placement and sizing is one of the current topics in restructured power system. Most of the authors have worked out on their optimum placement base on the power losses reduction concept. However, the improvement on power losses value in the network will not guarantee to the planner to have lower voltage stability index (VSI) for the system. This paper proposes a new approached for multi DG placement and sizing for distribution systems which is based on a voltage stability index. The most optimum DG size will be found out using several types of PSO optimization algorithm. The output results will also compared with EPSO, REPSO, and IPSO. The proposed algorithm is tested on 12-bus, modified 12-bus and 69-bus radial distribution networks.